2017
DOI: 10.1128/aac.02464-16
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Tuberculosis Treatment Outcome in Adult Patients Treated with Thrice-Weekly Regimens in India

Abstract: The Indian Revised National Tuberculosis (TB) Control Programme uses thrice-weekly treatment with standard drug dosages. The role of plasma drug levels and other factors in determining TB treatment outcomes is not well understood. We aimed to determine the factors influencing the concentrations of rifampin (RMP), isoniazid (INH), and pyrazinamide (PZA) at 2 h postdosing in adult TB patients and to study the factors impacting TB treatment outcome. We recruited 1,912 adult TB patients (newly treated and retreate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 34 publications
2
31
3
Order By: Relevance
“…In this study, the overall TB treatment success rate is higher from previous published studies in different countries; studies from India reported the overall treatment success rates were (81%) [23], (83%) [24], (84.21%) [25], and (86%) [26], in Thailand the success rate was (78.5%) for patients in the TB Case Management cohort, while the success rate is high (87.5%) for patients in the National Health Security Office cohort [27], Iran (83.1%) [28], Uzbekistan (83%) [29], Denmark (80.5%) [30], Malaysia (67.26%) [31], Ethiopia (85.6%) [32], Somalia (81.8%) [33], Nigeria (83.1%) [34], in…”
Section: Discussioncontrasting
confidence: 59%
“…In this study, the overall TB treatment success rate is higher from previous published studies in different countries; studies from India reported the overall treatment success rates were (81%) [23], (83%) [24], (84.21%) [25], and (86%) [26], in Thailand the success rate was (78.5%) for patients in the TB Case Management cohort, while the success rate is high (87.5%) for patients in the National Health Security Office cohort [27], Iran (83.1%) [28], Uzbekistan (83%) [29], Denmark (80.5%) [30], Malaysia (67.26%) [31], Ethiopia (85.6%) [32], Somalia (81.8%) [33], Nigeria (83.1%) [34], in…”
Section: Discussioncontrasting
confidence: 59%
“…Furthermore, the plasmatic levels of the anti-tuberculosis drugs, isoniazid, and pyrazinamide are lower in adult males than in females. This could be related to the worst outcome in the treated males [ 108 ]. Interestingly, this higher proportion of affected males is not observed in children or young adolescents, suggesting the participation of sex hormones in the pathogenesis of tuberculosis [ 109 , 110 ].…”
Section: Bacterial Infections In the Respiratory Tractmentioning
confidence: 99%
“…12 The prevalence of unsuccessful tuberculosis treatment outcome was reported in different studies; Afar (18.2%), 13 West Ethiopia (17.5%), 3 Central Africa (27.6%), 14 and India (14%). 15 The studies showed that there are different factors for poor TB treatment outcomes. Older age, type of tuberculosis, TB/HIV comorbidity, previous tuberculosis treatment, low income, limited access to transport, distance from home to the treatment center, limited interest in information about the disease and its treatment, limited social support, multidrug resistance, and comorbidity have all been found to be related to unsuccessful treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%